Analisis Pengaruh Persepsi Kualitas Terhadap Kepuasan Dan Loyalitas Pelanggan - Tarumingkeng, Peter Jefferson (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
The test results in this study indicate that perceived quality does not significantly affect Customer Satisfaction in Toyota car buyers in Manado City. Thus the hypothesis which states that there is a significant effect of perceived quality on customer satisfaction is rejected. Quality perception has a significant positive effect on customer loyalty variables in Toyota car buyers in Manado City. Thus the hypothesis which states the perceived quality is assumed to have a significant positive influence on customer loyalty is accepted. Customer satisfaction has a significant positive effect on customer loyalty to Toyota car buyers in Manado City. Thus the hypothesis that customer satisfaction is suspected to have a significant positive influence on customer loyalty is acceptedKeywords: Perception, Quality, Customer Satisfaction and Loyalty